Strategi Operasional dan Pemeliharaan Preventif untuk Meningkatkan Keandalan dan Kinerja Alat Rubber Tyred Gantry (RTG) di Pelabuhan - Romadhon, Mukhammad Alginat (Peneliti.net, 2024)
The implementation of operational and preventive maintenance strategieson Rubber Tyred Gantry (RTG) equipment in ports has significantlypositive impacts on reliability, operational efficiency, and environmentalsafety. Through regular maintenance and periodic monitoring, the risks ofequipment damage and system failures can be minimized, consequentlyreducing unexpected downtime and enhancing overall equipmentavailability. Additionally, the adoption of these strategies brings benefitssuch as better cost control and increased operational productivity for theport. The success of these strategies relies on commitment, discipline inimplementation, and collaboration between operational and maintenancedepartments. These findings underscore the importance of preventivestrategies in improving port operational performance and sustainability.